Basic geriatric principles for colorectal surgeons: How to optimize assessment and care of older patients in the perioperative period. Issue 3 (March 2020) - Rostoft, S.; Hamaker, M.E.
Abstract: Background: The majority of patients with colorectal cancer are older. For surgeons dealing with older patients, it is important to recognize patients that are frail and have an increased risk of complications and mortality. In this review, we will go through pre-treatment assessment, peri-operative management, as well as discharge planning and rehabilitation. Methods: This review is based on searching the literature for studies regarding colorectal cancer, frailty, cognition, patient preferences and geriatric assessment as well as the academic and clinical experience of the authors. Results: In the pre-treatment assessment, surgeons need to consider capacity to consent, patient preferences, frailty and life-expectancy, risk of complications, and whether the patient can be optimized before surgery. Then, the patient and treatment options should be discussed at a multidisciplinary team meeting. When the patient is admitted for surgery, discharge planning should start immediately, and if complications such as delirium or falls occur, the patient should be co-managed with geriatric services. Conclusion: Frail older adults with colorectal cancer need a tailored approach from pre-treatment assessment until discharge after surgery, and co-management with a geriatrician is recommended. If this is not possible, surgeons treating frail older patients may improve care by adapting some geriatric principles.